2012
DOI: 10.5559/di.21.3.07
|View full text |Cite
|
Sign up to set email alerts
|

Rizični Čimbenici Eksternaliziranih Ponašanja I Odstupajućih Navika Hranjenja Među Adolescentima

Abstract: Cilj ovog istraživanja bio je ispitati relativan doprinos rizičnih čimbenika iz različitih domena (odnosi u obitelji i s vršnjacima te osjećaj pripadnosti školi) u objašnjavanju eksternaliziranih ponašanja (agresivnoga i rizičnoga spolnog ponašanja) i odstupajućih navika hranjenja mladića (n=429) i djevojaka (n=307) iz opće populacije između 15 i 20 godina. Kako bi se ispitala prediktivna snaga ispitivanih varijabli za predviđanje eksternaliziranih ponašanja i odstupajućih navika hranjenja kao kriterijskih var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
3
3
0
Order By: Relevance
“…Although we did not find a serial mediation link, we found significant relations between the measured variables similar to other studies in Croatia (e.g. Livazović & Ručević, 2012;Šincek & Ajduković, 2012). More specifically, it was shown that poor parenting/supervision, as well as more deviant peer association, is related to the delinquency of both adolescent males and females.…”
Section: Discussionsupporting
confidence: 89%
“…Although we did not find a serial mediation link, we found significant relations between the measured variables similar to other studies in Croatia (e.g. Livazović & Ručević, 2012;Šincek & Ajduković, 2012). More specifically, it was shown that poor parenting/supervision, as well as more deviant peer association, is related to the delinquency of both adolescent males and females.…”
Section: Discussionsupporting
confidence: 89%
“…These results suggest that eighth-graders were able to recognize more forms and elements of various unacceptable behaviours, both in peer relationships and personally, especially when it comes to nonphysical forms of violence, lying and gossiping in particular. Similar results are indicated in the research by Livazović and Vranješ (2012), who state that older learners are more often victims of spreading lies and gossip compared to their younger peers and explain that nonphysical forms of violence are more present in older learners and that the tendency to quarrel increases with learners' age. Table 3 also shows that eighth-graders' assessments are higher than seventh-graders' in composite variables related to assessments of parental behaviours with regard to consumption of alcohol, cigarettes, and playing games of chance.…”
Section: Measuring Instrument and Research Methodssupporting
confidence: 87%
“…(Gottfredson, Wilson, 2003;Gottfredson et al, 2002). The sense of belonging to school and school success proved to be significant negative predictors of aggressive and risky sexual behavior (Livazović, Ruĉević, 2012;Lonczak et al, 2002). Namely, according to some authors (Hirschi, 1969), young people who establish positive social relations with school, unlike those who fail to do so, more often manifest prosocial behaviors (eg helping other students) and succeed in realizing their academic potential.…”
Section: Discussionmentioning
confidence: 99%